Quantitative impacts of alternative East Asia free trade areas: a CGE assessment - Kitwiwattanachai, Anyarath (2008)
The aim of this thesis is to make a comprehensive assessment and comparison of the quantitative economic impacts at both the domestic and the international level of four alternative FTA options in East Asia - ASEAN-China, ASEAN-Japan, ASEAN-Korea and East Asia - by using a static multi-region, multi-sector CGE model as a tool. With two main extensions to the "standard" CGE model in this study - the introduction of unemployment and the incorporation of highly disaggregated household data (Thailand is a case study) - the analysis is enhanced on the issues of labour markets and poverty and the income distribution.